Knowledge and practice of standard precautions in public health facilities in Abuja, Nigeria - Okechukwu, Emeka Franklin; Motshedisi, Chauke (International Journal of Infection Control, 2012)
Adherence to standard precautions is poor in public health facilities in resource-limited settings due to higher disease prevalence and limited organizational support. The practice of standard precautions among Health Care Workers (HCWs) in public health facilities in Abuja, Nigeria was evaluated. A cross-sectional survey of 277 HCWs was conducted using a structured questionnaire. Of 277 participants, 83(29.96%) were doctors; 194(70.04%) were nurses. Median age (years) of doctors was 34(IQR: 30, 39), while nurses was 39(IQR: 33; 45). Median years of experience for doctors was 7(IQR: 4; 10) while nurses was 15(IQR: 9; 20). 16.61% participants had knowledge of the basic concept of standard precautions. 42.24% knew potential sources of occupational exposure. The association between the knowledge and area of practice was significant (p=0.011). 97.46% practiced hand washing; 97.83% reported regular use of hand gloves; 88.44% use gown or plastic apron; 68.95% use masks and eye protector. The major factor reported for non-adherence was non-availability of the materials. Practice of recapping used needle was common among doctors than nurses (p=0.01). 32.53% of doctors and 28.87% of nurses had ≥1 dose of hepatitis-B vaccine; the difference in hepatitis-B immunization status of doctors and nurses was not significant (p=0.556). The knowledge of standard precautions among HCWs was suboptimal. Except for mask and eye protector, the use of PPE was good. Non-availability of materials was the major cause of poor compliance. The HCWs hepatitis-B vaccination status was poor. Capacity development of HCWs and a comprehensive infection prevention and control program were recommended.